Treatment and prognosis for retrograde cervical lymph node metastases in breast cancer - Qin, Rong; Zhang, Qiaoyu; Weng, Jianfeng; Liu, Weiping; Zhang, Bo; Lv, Gang; Wang, Yi; Wu, Youjun; Pu, Yongdong (Contemporary Oncology/Współczesna Onkologia, 2015)
Metastasis in axillary and supraclavicular lymph nodes has been frequently observed in patients with breast cancer. The clinical staging and therapeutic principle determined according to the situation of lymph node metastasis are clear. One patient with infiltrating ductal carcinoma of the left breast was reported to undergo modified radical mastectomy. One and a half years later, lymphadenectasis was observed in area II, III, IV, V and VI of the left neck; therefore, cervical lymphadenectomy was performed under cervical plexus anesthesia, indicating lymph node metastatic adenocarcinoma (21/26). The patient took 10 mg tamoxifen twice per day for five years after lymphadenectomy and the review showed negative results in liver, lungs, mediastinum, neck and contralateral breast. This suggested that although breast cancer complicated with retrograde cervical lymph node metastases is rare, timely surgery is required even if the patient is in a good general condition, to avoid „delayed therapy” due to misjudgment of illness simply according to disease staging.